Gym Interrupted - Coulter, Myrl (My Life at the Gym, 2012)
As a veteran of hundreds of workout classes, I have acquired a strange assortment of remnant clothing that lurks in the dark recesses of my closet: tiny shorts, striped tights, vicelike bra tops, and even leg warmers, all of which adorned my body at some time during the last twenty-five years. With such gym experience, you might expect that I’ve developed a female support network to sustain me during ups, downs, and in-betweens. Not exactly. Getting myself to the gym on a regular basis requires more fortitude, intestinal and otherwise, than I can consistently muster. After one of my prolonged